PERCEIVED INFLUENCE OF AUTOMATION AS A STRATEGIC RECORD MANAGEMENT INNOVATION IN THE 21ST CENTURY BUSINESS ENVIRONMENT IN ANAMBRA STATE (International Nexus Multidisciplinary Research Journal, 2025)
The main purpose of the study was to determine the perceived influence of automation as a strategic record management innovation in the 21st century business environment in Anambra State. Two research questions guided the study and two hypotheses were tested at 0.05 level of significance. The descriptive survey research design was adopted for the study. The population of the study comprised 148 managers of registered Information and Communication Technologies (ICT) firms in Anambra State. A researcher developed structured questionnaire which was validated by experts business managers was used to collect data for the study. The Cronbach Alpha reliability method was applied to the collected data, resulting in coefficient values of 0.84 and 0.88 for clusters 1 and 2, respectively. The overall reliability coefficient was 0.86. Mean, standard deviation and t-test was used to analyse data. The finding of the study revealed that automation improves records creation in the 21st century business environment in Anambra State to a high extent. The finding also revealed that automation improves records storage in the 21st century business environment in Anambra State to a high extent. The findings further revealed that gender did not influence the perception of business managers on the influence of automation as a strategic record management innovation in the 21st century business environment in Anambra State. Based on these findings, the researchers recommended, among other things, that Owners and managers of business organization should develop clear and comprehensive policies outlining the use of automated systems, including procedures for data security, access control, and privacy.